Retention and radiative forcing of black carbon in Eastern Sierra Nevada snow - Sterle, K.; McConnell, J.; Dozier, J.; Edwards, Peter; Flanner, M. (Copernicus GmbH, 2013)
Snow and glacier melt water contribute water resources to a fifth of Earth’s population.Snow melt processes are sensitive not only to temperature changes, but also changesin albedo caused by deposition of particles such as refractory black carbon (rBC) and5 continental dust. The concentrations, sources, and fate of rBC particles in seasonalsnow and its surface layers are uncertain, and thus an understanding of rBC’s effect onsnow albedo, melt processes, and radiation balance is critical for water managementin a changing climate. Measurements of rBC in a sequence of snow pits and surfacesnow samples in the Eastern Sierra Nevada of California during the snow accumulation10 and melt seasons of 2009 show that concentrations of rBC were enhanced seven foldin surface snow ( 25 ng g-1) compared to bulk values in the snow pack ( 3 ng g-1).Unlike major ions which are preferentially released during initial melt, rBC and continentaldust are retained in the snow, enhancing concentrations late into spring, untila final flush well into the melt period. We estimate a combined rBC and continental15 dust surface radiative forcing of 20 to 40Wm-2 during April and May, with dust likelycontributing a greater share of the forcing than rBC.